Managing TR4, a threat to banana industry - Thangavelu, R; Uma, S (Indian Horticulture, 2019)
Tropical race 4 (TR4) o f Fusarium oxysporum f . s p . cubense (Foc) that causes Fusarium wilt disease in Cavendish group of bananas is regarded as most devastating and can occur both under tropical and subtropical conditions. Fusarium wilt affected plants fail to yield bunch and the pathogen once introduced can survive in soil for more than 40 years even in the absence of the host. Of late, severe incidence of TR4 (>50%) is observed in Grand Naine banana in Bihar (Katihar and Purnea districts), Uttar Pradesh (Faizabad district), Madhya Pradesh (Burhanpur district) and Gujarat (Surat district). As the strain TR4 can spread through planting material, soils, irrigation water and bunch stalk, there is a chance for further spread of this disease rapidly to other banana-growing states, viz. Maharashtra, West Bengal, Odisha, Karnataka, Andhra Pradesh, Tamil Nadu and North-Eastern states. In this case, there is a possibility of incurring a heavy loss to Indian banana industry worth `50,000 crore annually as it mainly depends on Cavendish clones (Syn: Basrai, Robusta, Harichal, Grand Naine, Shrimanthi, Bhusaval and Pedda Pacha Arati) which occupy 55% of the total area under banana and would be catastrophic. Thus, Fusarium wilt in banana will be a serious threat to livelihood and sustainability to all stakeholders says Dr S Uma, Director, NRC for Banana, Tiruchirapalli.